Identifikasi Risiko Pada Produksi Paprika (Studi Kasus di CV Cantigi Kabupaten Garut, Jawa Barat) - Febrica Handryani; Sulistyodewi Nur Wiyono; Kuswarini Kusno; Dini Rochdiani (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2021)
Paprika is one of the leading commodities of horticulture in the provinces of West Java. West Java is the largest contributors to the national paprika in Indonesia, this leads to support the community welfare and regional development there. One of an area in West Java Province that produces paprika is CV Cantigi at Cikandang village of Garut Regency. CV Cantigi produces a variety of horticultural crops, but the main commodity is paprika. Every period CV Cantigi experienced various risk events in paprika production, thus making the productivity decrease. The purpose of this study is to identify the risks that occur in paprika production in CV Cantigi and determine the mitigation actions to minimize the risks that arise. This research uses descriptive qualitative method with the house of the risk analysis tool. The results showed that 25 risk events occurred in the process of paprika production in CV Cantigi. There are 3 mitigation actions for paprika production that is producing paprika plants under the shade because paprika plants need optimal temperatures to grow, making a planting calendar to determine when the right time to produce paprika, and making observations before pest control so that there is no wrong target with mitigation actions then it can be minimized or reducing the emergence of priority risk agents.